Perlindungan Hukum terhadap Anak sebagai Korban Eksploitasi Seksual Melalui Media Online - Fawwas Aufaa Taqiyyah Prastiwi; Aroma Elmina Martha (Fakultas Hukum Universitas Islam Indonesia, 2023)
The problem formulation of this research are: What is the scope of online gender-based violence (KBGO)? and How is legal protection for children as the victims of sexual exploitation through online media?. This research used juridic-empirical legal research method. The data was taken by collecting information which was conducted through interview and observation supported by legislation. The result of this research showed that: First, kinds of KBGO found in online media are in the form of cyber harassment, online grooming, sexting, impersonation, malicious distributions and cyber stalking; the operandi mode of KBGO by the perpetrators is to get their own satisfactory; the regulation related to KBGO is contained in the Electronic Information and Transactions (ITE) Law and the Pornography Law. Second, there have been several laws regulating sexual exploitation of children that contained in the Sexual Violence Legislation Act, the Electronic Information and Transactions (ITE) Law, the Pornography Law and the Child Protection Law; the legal protection given to victims begins at the consultation stage until the Inkracht decision; the implementation of law in providing protection among law enforcers is still different and overlapping. This study recommends that it maximizing the provision of legal protection and the implementation of Forensic Psychology; formed a task force to prevent and handle the children who are being the victims of online sexual exploitation that involve all regional, provincial, NGO (non-governmental organization), and police agencies.